2008
DOI: 10.1007/s11606-008-0612-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Health Literacy in Patients with Hypertension

Abstract: When controlling for cognitive and sensory variables, the association of age and education with STOFHLA scores was dramatically reduced. Thus, future interventions aimed at improving self-care for patients with low health literacy should aim to reduce demands on patients' cognitive abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 25 publications
(33 reference statements)
12
68
4
4
Order By: Relevance
“…23 In fact, there is a small but growing body of literature documenting associations between measures of literacy, health literacy, and limited sets of cognitive abilities. 15,[24][25][26][27] These studies support the premise that the impact of health literacy on outcomes might be explained by a wide array of cognitive domains. It is imperative to explore these links, as this will expand our thinking on the true nature of the problem, and improve our ability to develop more effective strategies for identifying and responding to individuals who will struggle to learn and apply health information.…”
Section: Objectivesupporting
confidence: 66%
“…23 In fact, there is a small but growing body of literature documenting associations between measures of literacy, health literacy, and limited sets of cognitive abilities. 15,[24][25][26][27] These studies support the premise that the impact of health literacy on outcomes might be explained by a wide array of cognitive domains. It is imperative to explore these links, as this will expand our thinking on the true nature of the problem, and improve our ability to develop more effective strategies for identifying and responding to individuals who will struggle to learn and apply health information.…”
Section: Objectivesupporting
confidence: 66%
“…One of the strengths of the numeracy assessment used in this report is that it is brief and does not require a neuropsychologist to administer or interpret it. Previous studies have identified cognitive deficiencies in the CKD and ESRD population (18 -21), and declining cognitive function has been implicated as a potential mediating factor of the lower health literacy documented among the elderly (22,23). Our study suggests a potential relationship between cognitive impairments and numeracy deficiencies in the CKD and ESRD population.…”
Section: Discussionsupporting
confidence: 52%
“…While multiple studies have documented the presence of cognitive deficits in CKD and ESRD (18 -21) and previous findings in patients with hypertension and congestive heart failure have established an association between cognitive performance and health literacy (22,23), there is a gap in our understanding of cognitive performance and numeracy. In this report, we describe the numeracy skills of an outpatient cohort of ESRD and stage 4 to 5 CKD patients assessed using a measure of analytical and statistical numeracy.…”
mentioning
confidence: 99%
“…In a study by Levinthal, Morrow et al, severity of the disease was significantly related to health literacy [10]. The results obtained by Pandit et al showed health literacy as an important predictor of blood pressure control [11].…”
Section: Introductionmentioning
confidence: 97%